The evaluation of collaborative synchronous learning environment within the framework of interaction and community of inquiry: An experimental study - Alper Aslan (Journal of Pedagogical Research, 2021)
This study aims to investigate a collaborative synchronous learning environment in terms of students' community of inquiry perceptions (cognitive, social, and teaching presences) and interaction levels. This quantitative study was conducted with the participation of fifty-nine freshmen (twenty-nine in the control group and thirty in the experimental group) in the department of Information Technologies at a university. The study lasted nine weeks, including two weeks of data collection and seven weeks of implementation procedure. After the implementation, the Community of Inquiry Scale and the Online Course Interaction Level Determination Scale were administered to the participants. The results revealed that co-operative synchronous learning experiences positively influenced students' community of inquiry perceptions and interaction levels in the experimental group. Further results and implications are discussed at the end.